2014
DOI: 10.1200/jco.2014.55.9070
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Stage After Neoadjuvant Chemotherapy Determines Survival After Surgery for Adenocarcinoma of the Esophagus and Esophagogastric Junction

Abstract: The stage of esophageal or esophagogastric junction adenocarcinoma after neoadjuvant chemotherapy determines prognosis rather than the clinical stage before neoadjuvant chemotherapy, indicating the importance of focusing on postchemotherapy staging to more accurately predict outcome and eligibility for surgery. Patients who are downstaged by neoadjuvant chemotherapy benefit from reduced rates of local and systemic recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
178
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(195 citation statements)
references
References 22 publications
13
178
1
3
Order By: Relevance
“…147 Some recent studies indicate that an increase in the time latencies between completed neoadjuvant therapy and surgery from currently 4-6 weeks to over 12 weeks may improve the tumour response to neoadjuvant therapy in OSCC and OAC, which may increase the rate of radical resection. 148,149 The optimal interval between neoadjuvant therapy and surgery in relation to survival is being assessed in an RCT (NCT02415101).…”
Section: Timing Of Surgery Following Neoadjuvant Therapymentioning
confidence: 99%
“…147 Some recent studies indicate that an increase in the time latencies between completed neoadjuvant therapy and surgery from currently 4-6 weeks to over 12 weeks may improve the tumour response to neoadjuvant therapy in OSCC and OAC, which may increase the rate of radical resection. 148,149 The optimal interval between neoadjuvant therapy and surgery in relation to survival is being assessed in an RCT (NCT02415101).…”
Section: Timing Of Surgery Following Neoadjuvant Therapymentioning
confidence: 99%
“…However, these thresholds may not be optimal: PERCIST is neither tumor-nor contextspecific, whereas the MUNICON threshold was derived from just 40 patients; furthermore, SUV max provides no spatial information. More fundamentally, both assess only the primary tumor; the high rates of disease recurrence seen even in patients with pathologically responsive primary tumors suggests important unidentified factors, perhaps involving nodal or distant micrometastases-a recent report described tumor downstaging after NAC (a reduction from pretreatment clinical to posttreatment pathologic stage) to be strongly associated with survival (14).…”
mentioning
confidence: 99%
“…Patients with ypIII or ypIV had a significantly poorer survival. Some studies have demonstrated the prognostic value of postoperative pathological findings including ypTNM (27,28), while other proposed that both pretherapeutic factors also worked as prognostic factors (29,30). Among these prognostic factors, postoperative pathological findings attracted more attention.…”
Section: Discussionmentioning
confidence: 99%